A FAIR TAX BASE FOR THE MUNICIPAL WASTE CHARGE – KEY TO AN EFFECTIVE WASTE MANAGEMENT POLICY IN THE REPUBLIC OF BULGARIA - Vania GEORGIEVA; Nadezhda BLAGOEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Municipal waste management is one of the most complex flows to manage. It is usually delegated to local authorities and funded by the revenue from the municipal waste charge. The critical introduction of the polluter pays principle raises the question of how to reasonably set the municipal waste charge. It should be structured so that it generates sufficient revenue to cover the costs of waste management. At the same time, it should influence human behaviour to reduce waste even at the source. Achieving both at the same time requires a strong link to the tax base of the charge. The fairest one is linked to the amount of household waste. Such a link is necessary to incentivise taxpayers to effectively reduce and manage the waste generated. Bulgaria is among the countries that have postponed such a reform for many years, but it is now becoming inevitable. The main objective of this study is to assess and analyse the current financial instruments and tax legislation related to municipal waste management in the Republic of Bulgaria. The critical point is to evaluate the link between the tax base and the taxpayers’ behaviour by setting the municipal waste charge in the Republic of Bulgaria. The methods of retrospective analysis and synthesis, inductive and deductive methods and comparative analysis are used to achieve the aims and objectives of the study. In Bulgaria, an unfair tax base has always been applied in determining the municipal waste charge. It depends not on the amount of waste but on the property’s tax assessment. The fiscal policy in Bulgaria related to the municipal waste management needs to be updated to achieve the targets set in the Bulgarian National Waste Management Plan 2021-2028. The change should affect both the methodology of calculating the waste charge to apply the "polluter pays" principle and the system of tax preferences and reliefs to encourage the rational treatment of household waste, such as recycling.